The Internationalization of Yen and Key Currency Questions - Iwami, Toru (IMF Working Papers; Working Paper ;, 1994)
The role of the yen in the International financial system is reconsidered from a comparative (historical) approach. Compared with the D-Mark in the postwar years, the limited use of the yen results not so much from regulations on capital movements as from the structure and behavior of Japanese economy. The history of the pound-sterling and the U.S. dollar reveals the fact that such factors as the network of foreign trade and economic size constitute the basis and 'inertia' of a key-currency. Thus for a currency to rise to a key-position in global transactions, real factors are more decisive than financial market arrangement. Seen from the foreign economic relations, it is not possible for Japan to own a key-currency independent from the U.S. dollar.